Studying of rock slope stability for southeastern plunge of Bekhair anticline, North Iraq - Mohammed Rashid Aboud; Ali Ismail Hassan (Tikrit Journal of Pure Science)
The research aims to study rock slope stability for southeastern plunge of Bekhair anticline north Iraq which formations (Bekhme, Shiranish, Kolosh) are cropped out in the area and assessment all factors affecting on stability such as discontinuities. Engineering classification according to[1] and [2], attitude of beds, slopes and friction angle of marl through studying of (4) stations represented the types of failures, occurs or probable to occur. The study shows that the slopes in the area are parallel concordant and discordant while the failures including the main modes of failures such as (Rock fall) in stations (1,3) Toppling in station (4) plane sliding probable in station (2) in addition to rock rolling which sometimes follows the above mentioned modes of failure